Antimony Sulphide Nanorods Decorated onto Reduced Graphene Oxide Based Anodes for Sodium-Ion Battery. (2020) - Dashairya, Love; Saha, Partha
Abstract: Sb2 S3 and Sb2 S3 /rGO nanorods were developed by a facile hydrothermal route and thoroughly investigated for their crystallinity, and phase evolution using XRD, FESEM/EDS, and FTIR analysis. The electrochemical sodium-ion charge storage behavior of the synthesized anodes was examined in CR-2032 type coin cells using galvanostatic charge-discharge measurements at a current of ∼50 mAg -1 . The preliminary galvanostatic cycling data shows that Sb2 S3, and Sb2 S3 /rGO exhibits a decent discharge and charge capacity of ∼601 mAhg -1, ∼256 mAhg -1, 528 mAh.g -1, and ∼399 mAh.g -1, respectively, for the first cycle with Coulombic efficiency ∼42.6% and ∼75.6%. It was found that rGO incorporation can salvage the capacity loss and improved Coulombic efficiency in the first cycle. However, the rapid capacity fades in the subsequent cycles warrant further in-depth studies to get an idea about the Na-ion storage behavior in the electrodes.